Resposta de cultivares de feijão (Phaseolus vulgaris L) à calagem e adubação fosfatada - Ronzelli Júnior , Pedro; Vieira , Clibas; Braga , José Mário; Sediyama, Carlos S (Revista Ceres, 2025)
At Piraquara, Paraná State, in soil with pH 4.9, 4.5 m.e. % of exchangeable aluminum, 1.4 m.e. % of calcium + magnesium, and 1 ppm. of phosphorus, it was studied the response of 17 bean cultivars to liming and phosphate fertilization.